2020
DOI: 10.1016/j.btre.2020.e00530
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome sequencing and comparative genome characterization of the lignocellulosic biomass degrading bacterium Pseudomonas stutzeri MP4687 from cattle rumen

Abstract: Highlights The isolation of P. stutzeri MP4687 from cattle rumen. The complete genome sequencing and comparative analysis of P. stuteri. Adaptation to the rumen environment. The strain has complete LCB hydrolyzing potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The biomass of P. kudriavzevii is rich in glycerol [42], which might be used as a substrate to promote the growth of Anaerovibrio. Our data showed that isolate 8 feeding increased the relative abundance of Pseudomonas, which can perform functions including hydrocarbon degradation, xenobiotic degradation, nitrification, denitrification, cellulose degradation and lipolysis [43][44][45]. The higher proportion of Pseudomonas may improve feed digestibility in Hu sheep.…”
Section: Discussionmentioning
confidence: 72%
“…The biomass of P. kudriavzevii is rich in glycerol [42], which might be used as a substrate to promote the growth of Anaerovibrio. Our data showed that isolate 8 feeding increased the relative abundance of Pseudomonas, which can perform functions including hydrocarbon degradation, xenobiotic degradation, nitrification, denitrification, cellulose degradation and lipolysis [43][44][45]. The higher proportion of Pseudomonas may improve feed digestibility in Hu sheep.…”
Section: Discussionmentioning
confidence: 72%
“…and Serratia spp. [59][60][61]. They usually produce enzyme systems for lignocellulose degradation, which comprises cellulase, xylanase and cellobiase.…”
Section: Typical Microorganisms For Lignocellulose Degradationmentioning
confidence: 99%
“…While salicin utilization has been observed in some Pseudomonas strains [ 13 , 14 ], those particular strains have not been identified in association with Populus [ 6 ]. Therefore, we hypothesized that another organism within the microbiome might act as a facilitator of the interaction between Populus and Pseudomonas species.…”
Section: Introductionmentioning
confidence: 99%